2020
DOI: 10.1007/s00158-019-02471-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficient limitation of resonant peaks by topology optimization including modal truncation augmentation

Abstract: In many engineering applications, the dynamic frequency response of systems is of high importance. In this paper, we focus on limiting the extreme values in frequency response functions, which occur at the eigenfrequencies of the system, better known as resonant peaks. Within an optimization, merely sampling the frequency range and limiting the maximum values result in high computational effort. Additionally, the sensitivities of this method are not complete, since only information about the resonance peak amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…For the iterative scheme discussed above, it is the largest thickness which is the problematic one, since automatically also the condition number is the largest one. For the computationally most efficient case with only one factorisation over the whole set, the iteration counts for the Krylov basis for t = 1/100 are (33,29,25,23), i.e., constant in relative terms. This is also the worst-case result.…”
Section: Other Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the iterative scheme discussed above, it is the largest thickness which is the problematic one, since automatically also the condition number is the largest one. For the computationally most efficient case with only one factorisation over the whole set, the iteration counts for the Krylov basis for t = 1/100 are (33,29,25,23), i.e., constant in relative terms. This is also the worst-case result.…”
Section: Other Considerationsmentioning
confidence: 99%
“…Wu et al have continued with a series of papers [21,22]. Moreover, Delissen et al [23] have studied this approach in the context of topology optimisation, where also the computational complexity can increase significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Takezawa [14] took the complex dynamic compliance as a novel objective function to lessen the resonant response by maximizing the energy dissipation near the resonance. Delissen et al [15] proposed a constraint function based on enhanced modal truncation to limit the frequency response peak at the resonance using an efcient reduced-order model. Furthermore, Kang et al [16,17] adopted the classical Rayleigh damping model to describe the energy dissipation of viscoelastic materials and found that the specifc design confgurations are sensitive to the damping coefcients.…”
Section: Introductionmentioning
confidence: 99%
“…the size of the model adopted for state estimation. The use of reduced model is widely proposed in the literature for simplifying both the model-based design (Palomba et al 2015;Xiao et al 2020;Delissen et al 2020) and the control synthesis (Caracciolo et al 2008). The model in (19) is therefore recast in the modal canonical form by using the linear transformation…”
Section: Introduction Of a State-observermentioning
confidence: 99%